Penerapan Disiplin Belajar Pada Siswa Kelas VIII Madrasah Tsanawiyah Swasta Hidayatullah Kupang NTT - Abidin Ahmad; Samsir Ramli (STAI Terpadu Yogyakarta, 2021)
The title of this research is the Application of Learning Discipline in Class VIII M. Private Students Hidayatullah Kupang. Based on preliminary observations, the researcher formulated the problem formulation, namely, how is the application of the discipline of MTs students, the factors that become obstacles in implementing the discipline of MTS students and the efforts made by the school in implementing discipline. The purpose of this research is to find out; How is the application of learning discipline in class VIII students of MTs Hidayatullah Kupan and then what are the factors that become obstacles in the application of learning discipline to students and How are the efforts of the principal and teachers in applying learning discipline to class VIII students of MTs Hidayatullah Kupang? The research method used is qualitative descriptive with data collection techniques, namely observation, interviews and documentation study with data analysis techniques, namely data reduction, data presentation and data verification. The results showed that there were several factors that became the obstacles in the application of learning discipline for grade VIII students such as; Lack of student awareness of learning discipline, less supportive learning environment, inadequate infrastructure, and examples / exemplary from students who are categorized as examples in the school environment. Furthermore, the application of learning discipline to students at MTs Hidayatullah Kupang in several ways including; Absent students at the beginning and end of the lesson, make rules about discipline, socialize the rules that have been made, give rewards / rewards for disciplined students, provide educational punishments for students who break the rules